Effect of emulsifier at different concentrations on the properties and characteristics of biodegradable films based on gelatin with palm oil for food packaging application - Zazalli, S. A.; B., Nabilah; De La Caba, Koro; Guerrero, Pedro; Zainal Abedin, Nur Hanani (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Biodegradable materials derived from polysaccharides, proteins and lipids are edible and have gained high concern nowadays due to the abilities and potential that can replace conventional plastics, thus it also can turn as food contact edible coatings and/or films. This work focused on the preparation and characterization of biodegradable films based on fish gelatin with enhanced flexibility by the incorporation of palm oil and different contents of an emulsifier. Emulsifiers act as surface active agents that capable in reducing the surface tension of the water-lipid interface or the water-air surface. The effect of emulsifier contents on physical, optical and mechanical properties of fish gelatin films was analyzed. The emulsifier addition caused a significant increase in film flexibility, without affecting other functional properties, such as water vapor permeability, solubility or color. Morphology analysis showed a better distribution of palm oil by using the emulsifier, indicating the beneficial effect of the combination of palm oil and emulsifier to manufacture flexible films.